Youth-Focused Programs in Collectivist Cultures: Can Youth-Focused Intervention Lead to Significant Change in Vulnerable Rural Communities in Armenia?. Issue 2 (3rd April 2022) - Devenish, Bethany; Hooley, Merrilyn; Mellor, David
Abstract: This study aims to evaluate whether community-based and individual interventions in Armenia lead to improvements in youth outcomes. Youth from eight schools were invited to participate in a community-based intervention plus a program targeting youth beliefs and behaviors, and youth from eight other schools were invited to participate in the community-based intervention alone. In total, 240 youths aged 10–16 years ( M  = 12.48; SD = 1.33) agreed to participate. There were significant increases in perceived sociopolitical control in both groups, and in emotional regulation through cognitive reappraisal in the community-based intervention-only group. The only significant change identified in the individual intervention group in comparison to the community-based intervention only group was a lower uptake of beliefs endorsing wife-beating. No other improvements were found. Our research failed to find support for brief interventions targeting the individual beliefs and behaviors of Armenian youth, indicating that multilevel interventions which are sustained over time may be needed.